Involution of classic Kaposi sarcoma lesions under acitretin treatment Kaposi sarcoma treated with acitretin. Issue 12 (22nd October 2020) - Daadaa, Najla; Souissi, Asmahane; Chaabani, Meryam; Chelly, Ines; Ben Salem, Moez; Mokni, Mourad
Abstract : Acitretin, indicated for generalized pustular psoriasis, was effective in concomitant classic Kaposi sarcoma.